Fei-Liu-Ping ointment inhibits lung cancer growth and invasion by suppressing tumor inflammatory microenvironment - Li, Weidong (BioMed Central, 2014)
BACKGROUND: Lung cancer is one of the leading causes of cancer-related mortality worldwide. Conventional chemotherapy and radiotherapy are the primary therapeutic methods for lung cancer with the use of combination therapies gaining popularity. The frequency and duration of treatment, as well as, managing lung cancer by targeting multiple aspects of cancer biology is often limited by toxicity to the patient. There are many naturally occurring anticancer agents that have a high degree of efficacy and low toxicity, offering a viable and safe approach for the treatment of lung cancer. The herbs traditionally used in Chinese medicine for anticancer treatment offer great potential to enhance the efficacy of conventional therapy. In this study, we evaluated the synergistic effects of Fei-Liu-Ping (FLP) ointment in treating lung cancer; a known anticancer Chinese herbal based formula. METHODS: In this study, A549 human lung carcinoma cell line and Lewis lung carcinoma xenograft mouse model were used. In addition, we utilized an in vitro co-culture system to simulate the tumor microenvironment in order to evaluate the molecular mechanisms of FLP treatment. RESULTS: FLP treatment significantly inhibited tumor growth in the Lewis lung xenograft by 40 percent, compared to that of cyclophosphamide (CTX) of 62.02 percent. Moreover, combining FLP and CTX inhibited tumor growth by 83.23 percent. Upon evaluation, we found that FLP treatment reduced the concentration of serum pro-inflammatory cytokines IL-6, TNF-α, and IL-1β. In addition, we also found an improvement in E-cadherin expression and inhibition of N-cadherin and MMP9. We found similar findings in vitro when we co-cultured A549 cells with macrophages. FLP treatment inhibited A549 cell growth, invasion and metastasis, in part, through the regulation of NF-κB and altering the expression of E-cadherin, N-cadherin, MMP2 and MMP9. CONCLUSIONS: FLP exerts anti-inflammatory properties in the tumor microenvironment, which may contribute to its anticancer effects. FLP treatment may be a promising therapy for inflammation associated lung cancer treatment alone, or in combination with conventional therapies and may prevent lung cancer metastasis.